Reviving Zakat and Waqf Institutions for Sustainable Community Developmentin Gombe State, Nigeria - Adamu Abubakar Muhammad; Hamza Abubakar Hussaini; Adam Muhammad Ardo (Indonesian Journal for Islamic Studies, 2024)
This paper aims to examine the current state of Zakat and Waqf institutions in Gombe State, Nigeria, and proposes measures for their revival for sustainable community development. The paper also covers a brief overview of the Islamic institutions of Waqf and Zakat, their importance in advancing social welfare and community development, and the present difficulties these organizations face in Gombe State, such as poor funding, improper management, and low public awareness. This study used a qualitative research design, collecting data through interviews and a review of the literature, and evaluating the data using content analysis. The study discovered that in order to revitalize these organizations and realize their full potential, a comprehensive strategy involving cooperation between government agencies, religious organizations, and the community must be looked in to. This strategy entails creating an efficient administration system, creating a thorough legislative framework for Waqf and Zakat, and raising public awareness through outreach and education initiatives.